PERSEPSI ORANG TUA TERHADAP PERKEMBANGAN ASPEK BAHASA PADA ANAK USIA DINI MELALUI PROGRAM PARENTINGDI TKK NEGERI BOGENGAN - Rabu, Sonia Agustin; Oka, Gde Putu Arya; Juita, Angelina Kurnia; Fono, Yasinta Maria (Bunayya, 2026)
This study aims to analyze parents' perceptions of early childhood language development and the factors influencing these changes through the parenting program at Bogenga State Kindergarten (TKK Negeri Bogenga). The main focus of the study is on shifts in parents' subjective views regarding their role in language stimulation, rather than simply evaluating children's developmental outcomes. The research design used was descriptive qualitative, with three parents of students aged 5-6 years old as subjects. Data were collected through in-depth interviews, observation, and documentation, which were then analyzed using the Miles and Huberman interactive model of reduction, presentation, and conclusion drawing. Data validity was ensured through a source triangulation strategy to determine the consistency of information between informants. The research findings are summarized in two main themes: positive perceptions of psychological comfort and openness of discussion through home visits compared to formal meetings at school, and indications of increased parental understanding in the practice of stimulating receptive and expressive language through immediate responses and verbal reinforcement. Observations indicated challenges in the consistency of children's focus and clarity of sentence structure that require follow-up through more structured language modeling at home.